Portraying Poverty: The Economics and Ethics of Factual Welfare Television. (September 2017) - De Benedictis, Sara; Allen, Kim; Jensen, Tracey
Since 2013 there has been an explosion of a new genre of factual programming on British television that centres on the everyday lives of people claiming benefits. The emergence of Factual Welfare Television (FWT) has coincided with intensifying public and political debates about poverty and the British welfare state, and has proved a deeply controversial and contested genre. While programme-makers have argued that FWT fulfils a public service mandate to inform audiences, critics have accused producers of making inaccurate, provocative and unethical television. Sociological enquiries into FWT have focused on the representations within these programmes and audience reception, arguing that these contribute to hardening anti-welfare sentiment. This article presents a complementary and urgent line of enquiry into FWT, locating it squarely within the conditions of its production by including questions of cultural labour, diversity in the workforce, and increasing competition and deregulation within broadcasting. We argue that market logics governing broadcasting discipline cultural workers and contribute to the production of reductive and stigmatising representations of social class and poverty. In doing so, we offer new insights into relationships between television production, representation and – consequently – consumption.